Review of codes of practice for the design of box culverts for recommendation for South African Bureau of Standards (SABS) - Mpeta-Phiri Namalima, Tina (Department of Civil Engineering, 2023)
The study is a comparative desk study of the application of the vertical earth load, traffic live load and the nominal earth pressure in the design methodology of culverts as outlined in TMH7 – Code of Practice for the design of highways bridges and culverts in South Africa Part 2, AASHTO LRFD Bridge Design specification and the DMRB volume 2 section 2 part 12 - BD31/01. It involves the theoretical design and analysis of five single cell reinforced concrete box culverts ranging from 2.1m to 6.0m under different fill depths ranging from 0 to 8.0m by applying load obtained using the three design manuals. The objective of this study is to analyze the methodology involved in estimating vertical earth load on a culvert as outlined in the design manuals to ascertain relevance of the formulae and procedure in TMH7 or/and to recommend the most effective approach for evaluating the vertical earth load on box culverts specific and appropriate for South Africa. By comparing the load derivation methodology outlined in ASHTO LRFD and BD 31/01 and analyzing the load forces obtained from the analysis. Box culverts are designed as rigid monolithic structures to withstand the maximum bending moment and shear force. The design involves the analysis of the various loads acting on the culvert with the weight of the overhead earth embankment being the most significant. The vertical earth load, live load and the lateral earth pressure acting on the culverts at various fill depth are manually derived from equations as outlined in the three design manuals. The culverts are modelled and analyzed in Prokon as two-dimensional plane frame structures using the frame analysis module by applying this load to determine maximum positive hogging moments, maximum negative sagging moments and maximum positive shear forces for each span for the top slab. The load forces obtained for each span are then plotted against the soil cover depth to illustrate the discrete load effect of the vertical earth load and live load on the culverts at varying fill height and to determine the relationship between the culvert geometry, soil cover depth and the applied load. The result of the analysis shows that an increasing non-linear relationship exists between the load effects, the soil cover depth, and the span length. The dead load effect increases with increasing fill depth and culvert span while the live load effect diminishes with increasing fill height and culvert span i.e., for culverts buried at shallow depths, the traffic live load is the most critical load but as the height of the soil cover increases the dead load becomes more significant until a point is reached where the live load is totally insignificant. The vertical earth loads obtained from TMH7 and BD31/01 are constant at a particular fill depth for each culvert despite the different span length. The vertical earth load for these two manuals is estimated from the soil cover depth and density, the load tabulated clearly is independent of the culvert geometry. The load obtained from AASHTO LFRD is the lowest and less than 20% of the load obtained from the other two design manuals. Unlike TMH7 and BD31/01, AASHTO LFRD considers the effect of the soil-structure interaction to adjust the vertical earth load on the structure which automatically reduces the load value. The vertical earth load values obtained from TMH7 and BD31/01 are generally more conservative as compared to those obtained from AASHTO LFRD.